A hybrid mode to enhance the downward route performance in routing protocol for low power and lossy networks. (April 2018) - Oh, Sukho; Hwang, DongYeop; Kim, Kangseok; Kim, Ki-Hyung
An IPv6 routing protocol for low power and lossy networks provides an IPv6 communication for a wide range of applications in multi-hop mesh networks. The routing protocol for low power and lossy networks defines the creation and management of downward routes with two modes of operations: storing and non-storing modes. The storing and non-storing modes have weaknesses for memory constraints and packet traffic overheads, respectively. The storing mode may cause routing failures due to constraints on memory in routers and the non-storing mode may cause packet fragmentation that can become a factor for packet delays or loss. Then the problems may degrade the downward route performance in routing protocol for low power and lossy networks. Therefore, in this article, we propose a hybrid mode that combines the advantages of the existing two modes to improve the performance of downward packet transmission in routing protocol for low power and lossy networks networks. The proposed hybrid mode uses a new routing header format. The routing information for packet delivery is distributed with the extended routing header. We implement the proposed hybrid mode in Contiki OS environment to compare with existing techniques. From the experiment, it was observed that the proposed hybrid mode can improve the performance of downward packet transmission. Therefore, with the proposed hybrid mode, it is possible to configure a network enable to be composed of many leaf nodes with constrained memory. We also discuss future works.